Defective morphologies kinetically formed in diblock copolymers under the cylindrical confinement. (18th May 2015) - Zhang, Tingting; Deng, Hanlin; Yang, Tao; Li, Weihua
Abstract: The self-assembly of diblock copolymers confined in nanopores with a macroscopically length has been investigated using the dynamic simulations of the time-dependent Ginzburg-Landau theory. Our results indicate that truly long-range ordered morphologies of single cylinder and stacked disks can be formed in macroscopically long nanopores when the pore size is located in the corresponding equilibrium region of the two phases. Whereas the free-energy difference between neighboring phases formed in larger nanopores, such as stacked disks and single helix, and single helix and double helix, becomes smaller, or even there are two degenerate states, e.g. left-handed and right-handed helical morphologies, coexisting morphologies composed of two or more phases are observed including coexisting stacked disks and single helix, left-handed and right-handed helices, single and double helical morphologies. A rich variety of defects are present at the interface of two different morphologies, and their formation is explained in the context of physical mechanisms. Graphical abstract: Highlights: Simulations to reveal the kinetics of structure formation in block copolymers confined in macroscopically long nanopores. Defective morphologies are usually observed except for the phases of single cylinder and stacked disks. Many interesting defects are explored at the interfaces of different phases in defective morphologies.